Glymphatic System in Ocular Diseases: Evaluation of MRI Findings - Manava, Panagiota; Eckrich, C.; Luciani, F.; Schmidbauer, J.; Lell, Michael; Detmar, K. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: There is growing evidence of leakage of gadolinium in an impaired blood-retina barrier. We investigated gadolinium enhancement in different eye compartments and correlated the enhancement with specific ophthalmologic diseases. MATERIALS AND METHODS: In a prospective clinical study (ClinicalTrials.gov Identifier: NCT05035251), 95 patients (63 with and 32 without ophthalmologic disease) were examined before and after gadolinium administration (20 and 120 minutes) with heavily T2-weighted FLAIR. The cohort was divided according to the location of pathology into anterior and posterior eye compartment groups. Relative signal intensity increase in the anterior eye chamber, vitreous body with retina, optic nerve sheath, and the Meckel cave was analyzed and correlated with the final clinical diagnosis. RESULTS: In patients with a disorder in the anterior eye compartment, significant signal intensity increases were found in the central anterior eye chamber (P 20 minutes ¼ .000, P 120 minutes ¼ .000), lateral anterior eye chamber (P 20 minutes ¼ .001, P 120 minutes ¼ .005), and vitreous body with retina (P 20 minutes ¼ .02) compared with the control group. Patients with pathologies in the posterior eye compartment showed higher signal intensity levels in the central anterior eye compartment (P 20 minutes ¼ .041) and vitreous body with retina (P 120 minutes ¼ .006). CONCLUSIONS: Increased gadolinium enhancement was found in the central and lateral anterior eye compartments and the vitreous body with retina in patients with anterior eye compartment disorders 20 and 120 minutes after contrast application, suggesting impairment of the blood-aqueous barrier. In patients with a disorder in the posterior eye compartment, pathologic enhancement indicated disruption of the blood-retinal barrier that allows gadolinium to diffuse into the vitreous body with retina from posterior to anterior, opposite to the known physiologic glymphatic pathway.
CRIS-Team Scopus Importer:2022-08-05